Optimalisasi Peran Kader dalam Pencegahan Stunting melalui Peningkatan Nutrisi Baduta dan Ibu Menyusui: Pencegahan stunting - Asmawati; Nur Elly; Kheli Fitria Annuril; Andhita Ratnadhiani; Pauzan Efendi; Betty Yosephine (Universitas Lancang Kuning, 2023)
Stunting is a health problem that contributes to child morbidity and mortality. Stunting prevention can be done through nutritional interventions. The high stunting prevalence in Seluma Regency is due to knowledge, culture, socio-economic and others. The purpose of the activity is to improve the children's nutrition and mothers to increase the child's growth and development to prevent stunting through cadres empowerment. The method of activities is the socialization of the first 1000 days of life, cadre training, education of lactations, giving additional nutrition, and cadre assistance. The targets are cadres and mothers. Assessment of knowledge through questionnaires, for the ability of cadres and lactation mothers by direct observation. The results showed an increase in the average knowledge of cadres by 10 points after training, an increase in the knowledge and skills of lactation mothers, exclusive breastfeeding at 57.17%, and good breastfeeding frequency at 85%. Optimizing cadres is useful in promoting nutrition to prevent stunting.